2018
DOI: 10.1111/pcn.12632
|View full text |Cite
|
Sign up to set email alerts
|

Identification of somatic mutations in postmortem human brains by whole genome sequencing and their implications for psychiatric disorders

Abstract: Our developed filtering and validation approaches will be useful to identify somatic mutations in the human brain. The vulnerability of neuron-expressed genes to mutational events suggests their potential relevance to neuropsychiatric diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
(101 reference statements)
2
8
0
Order By: Relevance
“…Previous research has indicated that C>T transitions account for ~80% of somatic SNVs in single neurons [44]. Although some of these C>T transitions were likely derived from artificial C>U deamination due to cell lysis during the preparation of single-cell samples [48], we also observed the same bias for C>T transition following a WGS analysis of bulk brain tissues, which were free from deamination during cell lysis [52]. Neurons have a characteristic 5mC at non-CpG sites and a relatively greater amount of 5-hydroxymethylcytosine (5hmC) than other tissues [72, 73].…”
Section: Biological Mechanisms Underlying Somatic Mutations In the Brainsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous research has indicated that C>T transitions account for ~80% of somatic SNVs in single neurons [44]. Although some of these C>T transitions were likely derived from artificial C>U deamination due to cell lysis during the preparation of single-cell samples [48], we also observed the same bias for C>T transition following a WGS analysis of bulk brain tissues, which were free from deamination during cell lysis [52]. Neurons have a characteristic 5mC at non-CpG sites and a relatively greater amount of 5-hydroxymethylcytosine (5hmC) than other tissues [72, 73].…”
Section: Biological Mechanisms Underlying Somatic Mutations In the Brainsupporting
confidence: 59%
“…In a recent study, we explored somatic mutations in human brain tissue from three healthy individuals via WGS at a depth of ~100×. Allele fractions were assayed and validated via target amplicon sequencing (TAS), ranging from 0.5 to 14% in bulk tissue obtained from the cortex, cerebellum, and liver [52]. The somatic mutations exhibited considerable spatial diversity; some mutations were observed in the brain but not the liver, while others were observed in the cortex but not the cerebellum.…”
Section: Somatic Mutations In the Brains Of Individuals Without Neuromentioning
confidence: 99%
“…Somatic mutations in the brain are often found in genes expressed in neurons 80 and, thus, may be involved in psychiatric disorders. 81 Increases of partially deleted mtDNA were reported in postmortem BD brains.…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…Somatic mutations in the brain are often found in genes expressed in neurons and, thus, may be involved in psychiatric disorders …”
Section: Post‐mortem Brain Studiesmentioning
confidence: 99%
“…We focused on refining the analysis to mainly discard false positives. Our filtering criteria were tailored to discard sequencing artifacts, similar to other studies using Haloplex and common sequencing datasets (22)(23)(24)(25)(26). Advantages of visual analysis are the comprehensive analysis for each variant, easy implementation across datasets; however, it can become labor-intensive.…”
Section: Discussionmentioning
confidence: 99%